Pemodelan Manajemen Energi Microgrid pada Sistem Bangunan Cerdas - FX Nugroho Soelami; Edi Leksono; Irsyad Nashirul Haq; Justin Pradipta; Putu Handre Kertha Utama; Aretha Fieradiella Pahrevi; Faizatuzzahrah Rahmaniah; Meditya Wasesa (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
From the electricity system point of view, smart buildings can be seen as an integration of a microgrid electricity network that connects solar PV, storage system, and building load distribution. The operation condition of the microgrid needs to be evaluated and optimized to obtain efficient and reliable performance. This contribution presents an energy management modeling for the microgrid optimization process in a smart building system. The energy sources connected to the microgrid are solar PV, battery storage system, and the PLN (utility) grid. Combinations of load scenarios are evaluated, which consists of building a lighting system, water pump, dan HVAC system. The optimization goal is to find the optimal estimation of Self Consumption (SC) and Self Sufficiency (SS) values. A simulation result before the optimization shows that the system is operating with SC of 63.2% and SS of 96.32%. After the optimization, the values become SC = 84.68% and SS = 83.27%. Therefore, the amount of energy sourced from the Solar PV system is increased and the microgrid is working more optimally.